Sanitary condition of poultry houses during broiler growing - O. I. Kasianenko; O. L. Nechyporenko; S. M. Kasianenko; O. M. Nesterenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2022)
In modern poultry farming, the problem of controlling microbiological contamination of poultry housing is essential and relevant. High levels of microbiological air pollution and abundant contamination of poultry production surfaces can be powerful and dangerous risk factors for the spread of opportunistic and pathogenic microflora. The health of poultry and its performance depends on the health and welfare of poultry houses іndustrial zone. Sanitary condition is an integral part of the overall operation of the process poultry farms. In the practice of industrial poultry entered, the term “biological fatigue”. We assessed the sanitary-bacteriological condition of poultry houses by the indicators of the total number of microorganisms in the air and by the isolation of pathogenic microorganisms. We determined the rates of bacterial contamination of surfaces and the air of poultry houses during the technological break-rearing broiler. The objects of the study were bacterial contamination of air and object poultry houses. Scientific research has been conducted on the technological break and release of objects from poultry. According to our study, we established high levels of microbiological air pollution in poultry houses on the 14th, 28-th, and 42-th day of broiler breeding. The total microbial count air of poultry houses does not meet sanitary standards. On the 14-th, 28-th and 42-th day, breeding broilers for meat in the poultry house bacterial contamination were 184.33 ± 43.52 thousand CFU/m3; 376.25 ± 84.84 thousand CFU/m3 and 786.68 ± 214.91 thousand CFU/m3. The article presents research results on poultry houses' sanitary and bacteriological indicators of leaching. We have established a high level of contamination of production surfaces. The isolates were: E. coli – (39.3 %), Salmonella spp., and Campylobecter spp. – (14.5 %), Streptococcus spp., S. aureus – 23.6 % Proteus ssp., Enterobacter ssp. – 22.6 %. The qualitative and quantitative composition of isolated microflora from poultry farms indicates significant risks of reducing the natural non-specific protective forces of the bird, the emergence of infectious diseases, and reduced productivity of birds. Thus, the sanitary condition of poultry houses is one of the main criteria for stable epizootic well-being in poultry and a guarantee of effective agribusiness.